Differences of Universal and Multiplex Primer for Detection of Dengue Virus from Patients Suspected Dengue Hemorrhagic Fever (DHF) in Surabaya - Ansori, Arif; Sucipto, Teguh; Deka, Pemta; Ahwanah, Nur; Churrotin, Siti; Kotaki, Tomohiro; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2015)
Dengue Hemorrhagic Fever (DHF) is a global health problem in tropical and subtropical regions, as well as endemic in110 countries around the world. Indonesia is one of the largest countries in the region of endemic dengue. In Indonesia, dengue virus infection has become a contagious disease that was very important and was reported in 1968. Many molecular epidemiological approaches have been developed to look for factor that has been assumed as the cause of the increase of prevalence dengue virus infection in the world. The aim of this study is for the detection and determination of serotype of dengue virus in Surabaya. The method used was the technique of Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and Polymerase Chain Reaction (PCR) with specific primers for dengue virus. Samples suspected DHF patients were obtained from various health center and hospital in Surabaya. Results of this research detected negative result for dengue virus in all samples of patients suspected DHF. Negative results caused by dengue virus titers in serum samples of patients who had been dropped due to long storage time and taken after the third day of fever in early period.